Nursing Schools in northeastern Brazil (1943-1975) - Djailson José Delgado Carlos; Maria Itayra Padilha; Mariana Vieira Villarinho; Miriam Süsskind Borenstein; Ana Rosete Camargo Rodrigues Maia (Rev Rene)
This is a qualitative, narrative and socio-historical study aimed at analyzing the creation of nursing schools in the Northeast of Brazil (1943-1975). The time frame corresponds initially to the creation of the first school and finally to the year in which all the northeastern states founded at least one training institution for nurses. The data collection happened between April and July 2013 using the collection of the Central Library of the Federal University of Santa Catarina and the Study Group about Nursing Knowledge History and Health. About these schools in the Northeast, it is highlighted that their expansion was increased after the University Reform. This situation allowed the local education, abolished the need to travel to other states in search of professional training, enabled a new scenario in educational and health institutions and improvements in health care.